2019
DOI: 10.3390/insects10040114
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Quality of Essential Oils and Their Synergistic Effect with Diatomaceous Earth, for the Control of Stored Grain Insects

Abstract: Essential oils (EOs) have gained increasing interest as a low-toxic, eco-friendly alternative to synthetic repellents and insecticides against insect pests. However, they have scarce practical application in the protection of stored grain because of their limited efficacy and their interference with the organoleptic properties of the grain. In this study, we evaluated the olfactory profile of the EOs of Foeniculum vulgare, Pistacia lentiscus, and Ocimum basilicum, and their toxicity against the main stored gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…This usually occurs when the doors are open to allow the unloading of the fresh meat and the loading of the hams. Even if EOs have been extensively studied as topical repellent against insects of medical or veterinary importance [20,[45][46][47], and proposed as repellents in food packaging [48][49][50][51] and stored foodstuff [18,44,52], to the best of our knowledge, this is the first report on the use of an EO-charged mist as an olfactory barrier to protect an indoor working space from the entrance of problematic flies. In line with our results, however, a good efficacy of the EOs as aerosol spray have been reported by Revay et al [53] who observed that a timed-released 0.3% aqueous geraniol emulsion significantly reduced mosquito-biting pressure of Culex pipiens L. and Aedes albopictus Skuse (Diptera: Culicidae) in outdoor conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This usually occurs when the doors are open to allow the unloading of the fresh meat and the loading of the hams. Even if EOs have been extensively studied as topical repellent against insects of medical or veterinary importance [20,[45][46][47], and proposed as repellents in food packaging [48][49][50][51] and stored foodstuff [18,44,52], to the best of our knowledge, this is the first report on the use of an EO-charged mist as an olfactory barrier to protect an indoor working space from the entrance of problematic flies. In line with our results, however, a good efficacy of the EOs as aerosol spray have been reported by Revay et al [53] who observed that a timed-released 0.3% aqueous geraniol emulsion significantly reduced mosquito-biting pressure of Culex pipiens L. and Aedes albopictus Skuse (Diptera: Culicidae) in outdoor conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Insects vectors of microorganisms are responsible for the loss and spoilage of a huge quantity of food and the spread of foodborne disease [ 1 ]. Spices EOs are widely used as a food ingredient for their aroma and preservative properties [ 56 ], and their toxic and repellent activity against food insect pests is reported in the literature [ 19 , 20 , 22 , 57 ], but very little is known about their use against synanthropic flies. Here, for the first time, we tested three oregano EOs chemotypes as insecticides and repellents against the blowfly C. vomitoria , which is a synanthropic fly vector of foodborne diseases.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the essential oils (EOs) of aromatic plants are characterized by low toxicity toward mammalians and high biodegradability [ 18 ]. Moreover, EOs of aromatic plant species, commonly used as food spices, have the advantage of being legally allowed in food and to have a smell profile already accepted by consumers [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…When observing the combinations of oils and oil isolated in the direct application route, we found that these results suggested a synergistic action between these oils, where one intensifies the action of the other, depending on the combination. Pierattini et al [27] using three essential oils [Foeniculum vulgare Miller (Apiaceae), Pistacia lentiscus L. (Anacardiaceae) and Ocimum basilicum L. (Lamiaceae)], found a synergistic effect between oil combinations, especially for those containing F. vulgare, that obtained greater efficacy in the mortality of target individuals. Still in this sense, the combination of 90:10% neem oil and jatropha was the treatment with the lowest mortality (15.32%), in direct application, equaling the results presented by the witness.…”
Section: Resultsmentioning
confidence: 99%